A Novel Three-phase Rectifier Based on Improved PID Control Algorithm - Zhang Shutuan; Jiang Jing; Zhang Kai (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The three-phase rectifier based on traditional PID control algorithm can improve its harmonic effect, and increase its power factor, but it can’t overcome the problems of selection difficulty of the PID parameters and can realize the online self-turning function of the PID parameters. In order to deal with the questions, the three phase rectifier based on neural network PID control algorithm is designed in this paper. In this paper, the PID parameters of the novel rectifier can realize the function of the online self-turning, which increases the design efficiency and the control accuracy. The simulation results show that the three phase rectifier based on improved PID control algorithm can decrease the harmonic pollution and increase its power factor. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1910